Faktor Penerimaan Teknologi Shopee di Kalangan Mahasiswa: Integrasi Model TAM dan TPB - Holdani Nurrafi; Marsyanda Firlyandita; Ahmad Rafasyah Ramadhan; Akbar Pangestu; Virdha Aulia Rahma (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to analyze the factors that influence the acceptance of Shopee e-commerce technology among students with an integrative approach between the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). External constructs such as perceived trust, perceived security, and innovativeness are also included to strengthen the model. This study uses a quantitative approach with a descriptive-verification design and Structural Equation Modeling (SEM) analysis technique. Data were collected through an online questionnaire answered by 135 active Shopee student users. The results of the analysis show that perceived ease of use has a significant effect on perceived usefulness and attitude toward usage, while perceived usefulness also has a significant effect on attitude and intention to use. Social factors such as subjective norms, as well as psychological factors such as trust and security have been shown to have a positive effect on usage intention. However, perceived behavioral control does not have a significant effect. This study provides a theoretical contribution to the modeling of digital technology adoption and has practical implications for e-commerce industry players in developing strategies based on student users.